Unprecedented surface stabilized InP quantum dots with bidentate ligands - Seo, Haewoon; Bang, Meehee; Kim, Yongjin; Son, Chaeyeon; Jeon, Heung Bae; Kim, Sang Wook (RSC Advances, 2020)
For InP-based QDs, the current technology does not outperform CdSe-based QDs in many respects, one of which is stability. The optical stability of QDs is closely related to their surface properties, so QDs often use organic ligands for surface protection. These organic ligands are dynamically attached and detached on the QD surface; during detachment, their surfaces are easily damaged and oxidized, thereby deteriorating their optical characteristics. Therefore, we have synthesized a ligand 1,2-hexadecanedithiol with a bidentate form, inducing one ligand to bind to the QD surface strongly through the chelate effect, as a good way to improve the stability of the QDs; thus, the PL stability of the green-light-emitting InP-based QDs was greatly increased. To confirm the existence of the dithiol ligand, we used thermogravimetric analysis/simultaneous thermal analysis-mass spectroscopy (TGA/STA-MS). After that, we applied the ligand to blue-light-emitting ZnSe QDs and red-light-emitting InP QDs, and for those two types of QD we also confirmed that the stability was increased. Additionally, we tested dithiol exchanged QDs at a high temperature of 150 °C, and the increase of stability was effective even in a high temperature condition.
Keywords: Bidentate ligands; Blue light-emitting; Current technology; High temperature condition; Mass spectroscopy; Optical characteristics; Optical stability; Surface protection